BVRCIC Observations, Analysis, and Spectra of The Most Extreme Mass Ratio (Totally Eclipsing) W UMa Binary, V1187 Herculis. (27th March 2019) - Caton, Daniel; Gentry, Davis R.; Samec, Ronald G.; Chamberlain, Heather; Robb, Russell; Faulkner, Danny R.; Hill, Robert
Abstract: CCD, BVRI primary light curves of V1187 Her were taken in 2017 May and 2018 May at the Dark Sky Observatory in North Carolina with the 0.81-m reflector of Appalachian State University. A spectrum was taken earlier at Dominion Astrophysical Observatory (DAO) with the 1.8 m telescope. The spectral type is F(8.5 ± 1)V, resulting in a surface temperature of 6250 ± 125 K (Cox 7 ), so solar-type activity is expected. V1187 Her was previously identified as a low-amplitude, short-period, over-contact eclipsing binary (EW) with an orbital period of 0.310726 d. Strikingly, despite its low amplitude (∼0.15 mag), the early light curves show a total eclipse (eclipse duration: 31.5 minutes). This can only occur (in the absence of a strong third light) if the binary is an exceptionally extreme mass ratio binary, perhaps the most extreme known. Eight instances of minimum light were calculated. A 12-year period study reveals a secular period decrease in the orbital period with good confidence. The rate of period change is dP/dt = −1.5 × 10 −07 d/yr, probably due to magnetic braking. Its Roche Lobe fill-out is found to be a hefty 84% along with a mass ratio of only ∼0.044; indeed, the most extreme known among solar-type (i.e., W UMa) binaries. It has a cool spot region. The secondary component has a temperature of ≈ 6680 K, which makes it a W-subtype binary (the less massive component is hotter). The inclination is only ∼67° despite its total eclipses. A q-search was conducted, which showed the 0.044 value was the best fit to the light curves. Additionally, follow-up observations were taken on 2018 May 4, which confirmed the mass ratio found from the earlier curves.